2007
DOI: 10.1371/journal.pone.0000237
|View full text |Cite
|
Sign up to set email alerts
|

The CD34-Related Molecule Podocalyxin Is a Potent Inducer of Microvillus Formation

Abstract: BackgroundPodocalyxin is a CD34-related transmembrane protein involved in hematopoietic cell homing, kidney morphogenesis, breast cancer progression, and epithelial cell polarization. Although this sialomucin has been shown to block cell adhesion, the mechanisms involved remain enigmatic. It has, however, been postulated that the adaptor proteins NHERF-1 and 2 could regulate apical targeting of Podocalyxin by linking it to the actin cytoskeleton.Principal FindingsHere, in contrast, we find that full-length Pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 39 publications
4
91
0
Order By: Relevance
“…We never observed delivery of Crumbs3a to the periciliary region. Crumbs3a forms stable attachments with a submembranous anchoring complex that includes the proteins PALS and PATJ (Makarova et al, 2003), and transmembrane gp135 has been shown to interact directly with cytoskeletal components (Ojakian and Schwimmer, 1988;Li et al, 2002;Nielsen et al, 2007;Yu et al, 2007;Francis et al, 2011). Thus, we next wished to examine the behavior of a membrane protein that cannot participate in such interactions.…”
Section: Resultsmentioning
confidence: 99%
“…We never observed delivery of Crumbs3a to the periciliary region. Crumbs3a forms stable attachments with a submembranous anchoring complex that includes the proteins PALS and PATJ (Makarova et al, 2003), and transmembrane gp135 has been shown to interact directly with cytoskeletal components (Ojakian and Schwimmer, 1988;Li et al, 2002;Nielsen et al, 2007;Yu et al, 2007;Francis et al, 2011). Thus, we next wished to examine the behavior of a membrane protein that cannot participate in such interactions.…”
Section: Resultsmentioning
confidence: 99%
“…1); by western blotting and immunofluorescence confocal microscopy, expression of PC is low or not detected, respectively (Nielsen et al, 2007;Sizemore et al, 2007;Somasiri et al, 2004). In order to study the molecular function of PC in breast epithelial cells, others and we have ectopically expressed full-length PC and a series of structural mutants in MCF7 (Fig.…”
Section: Podocalyxin's Function In Epithelial Architecture and Morphomentioning
confidence: 99%
“…Overexpression of full-length PC (FL) in MCF7 results in apical bulging of monolayers, reduced transepithelial resistance (i.e., disrupted cell junctions), delamination and shedding of cells from monolayers in vitro (Nielsen et al, 2007;Somasiri et al, 2004). Strikingly, expression of PC in MCF7 (and MDCK) potently induces formation of apical microvilli.…”
Section: Podocalyxin's Function In Epithelial Architecture and Morphomentioning
confidence: 99%
See 1 more Smart Citation
“…Podocalyxin is a member of the CD-34-related family of sialomucins [3][4][5][6][7][8]. Podocalyxin was originally cloned from the human kidney as a component of the podocyte cell glycocalyx, while it was also identified on vascular endothelium and hematopoietic cells [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%